2004
DOI: 10.1016/j.ehj.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Current PTCA practice and clinical outcomes in The Netherlands: the real world in the pre-drug-eluting stent era

Abstract: In this unselected series of consecutive patients treated for stable and unstable angina in everyday clinical practice in the pre-drug-eluting stent era, clinical restenosis after 9 and 12 months follow-up of the patients occurred in 10.2% and 12.0%, respectively. The risk varies from 8.3% to 17.6% depending on the number of risk factors. A proper selection of patients that benefit from new devices warranted, since the vast majority are well-treated with standard techniques and proper assignment of expensive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 18 publications
1
60
1
2
Order By: Relevance
“…141 These UK figures are therefore consistent with the rates from Liverpool quoted in our study. Evidence from other international studies shows comparable results in unselected patients in Canada (8.2%), 124 Switzerland (12.1% TVR with a more severe case mix) 82 and The Netherlands (9.6% TVR), 142 reinforcing confidence in the reliability of the CTC Liverpool data, where the combined elective/non-elective rate was 8.8%. In the USA, generally higher rates of repeat revascularisation are reported in registry studies: Ellis and colleagues 143 obtained an overall rate of 13.4% for patients treated between 1994 and 2001, with 54% of patients in risk subgroups with rates <10% and a further 33% with a risk of 12.1%; Wu and colleagues 144 used a cohort treated in 1999 including unstented PCI with an overall rate of 16.2%.…”
Section: Are the Ctc Data Reliable And Representative?supporting
confidence: 50%
See 1 more Smart Citation
“…141 These UK figures are therefore consistent with the rates from Liverpool quoted in our study. Evidence from other international studies shows comparable results in unselected patients in Canada (8.2%), 124 Switzerland (12.1% TVR with a more severe case mix) 82 and The Netherlands (9.6% TVR), 142 reinforcing confidence in the reliability of the CTC Liverpool data, where the combined elective/non-elective rate was 8.8%. In the USA, generally higher rates of repeat revascularisation are reported in registry studies: Ellis and colleagues 143 obtained an overall rate of 13.4% for patients treated between 1994 and 2001, with 54% of patients in risk subgroups with rates <10% and a further 33% with a risk of 12.1%; Wu and colleagues 144 used a cohort treated in 1999 including unstented PCI with an overall rate of 16.2%.…”
Section: Are the Ctc Data Reliable And Representative?supporting
confidence: 50%
“…Other recent studies, based on unselected patient data, have developed independent risk 142 found diabetes to be required unequivocally as an independent predictor in a multivariate analysis. Hence the CTC models are in no way discredited by the omission of specific variables conventionally presumed to be important.…”
Section: Why Do Identified Risk Factors Differ From Those Expected?mentioning
confidence: 99%
“…Aegma et al reported a 10.3% target-vessel revascularization rate in a series of 3,146 patients followed for 9 months, 5 and Ellis et al reported an overall repeat revascularization rate of 13.4%. 6 In contrast, some randomized DES trials report BMS reintervention rates as high as 22.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Processes involved in AVF patency, particularly vascular smooth muscle cell proliferation and inflammation, also play a key role in the development of coronary restenosis after percutaneous coronary intervention (13). In contrast with the scarcely available data on genetic determinants of AV access failure, the genetic background of coronary restenosis has been more established (12,13). Although our SNP selection covered a wide range of candidate genes in all involved mechanisms, the obtained results do not indicate an important role for our selected SNPs in the development of AVF failure.…”
Section: Discussionmentioning
confidence: 93%
“…Excessive accumulation of extracellular matrix is mediated by several growth factors (5,9,11). Morphologically, these stenotic lesions closely resemble restenotic lesions after percutaneous coronary intervention (12,13). Additional specific pathophysiologic stimuli for intimal hyperplasia in vascular access stenosis include the abnormal calcium/phosphate metabolism in patients with CKD that result in arterial as well as venous calcification of the tunica media (14).…”
Section: Introductionmentioning
confidence: 99%